2021
DOI: 10.1155/2021/2989974
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Irisin Attenuates Oxidative Stress, Mitochondrial Dysfunction, and Apoptosis in the H9C2 Cellular Model of Septic Cardiomyopathy through Augmenting Fundc1‐Dependent Mitophagy

Abstract: In the present study, we used lipopolysaccharide- (LPS-) stimulated H9C2 cardiomyocytes to investigate whether irisin treatment attenuates septic cardiomyopathy via Fundc1-related mitophagy. Fundc1 levels and mitophagy were significantly reduced in LPS-stimulated H9C2 cardiomyocytes but were significantly increased by irisin treatment. Irisin significantly increased ATP production and the activities of mitochondrial complexes I and III in the LPS-stimulated cardiomyocytes. Irisin also improved glucose metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 71 publications
1
29
0
Order By: Relevance
“…Interestingly, Wang et al ( Wang et al, 2021 ) proposed that FUNDC1 was an integral mitochondrial outer-membrane protein that could increase the expression of VEGF and promote endothelial cell angiogenesis. Similarly, FUNDC1 not only alleviates ischemia–reperfusion injury but also inhibits apoptosis ( Wang et al, 2018 ; Jiang X. et al, 2021 ; Cai et al, 2021 ; Li et al, 2021 ). In our study, we observed that MLT treatment reduced the area of ischemic necrosis of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wang et al ( Wang et al, 2021 ) proposed that FUNDC1 was an integral mitochondrial outer-membrane protein that could increase the expression of VEGF and promote endothelial cell angiogenesis. Similarly, FUNDC1 not only alleviates ischemia–reperfusion injury but also inhibits apoptosis ( Wang et al, 2018 ; Jiang X. et al, 2021 ; Cai et al, 2021 ; Li et al, 2021 ). In our study, we observed that MLT treatment reduced the area of ischemic necrosis of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…However, after FUNDC1 knockdown in cardiomyocytes, the regulatory mechanisms of irisin on oxidative stress, mitochondrial energy metabolism, and mitophagy in cardiomyocytes were eliminated, and the caspase-3/caspase-9-mediated apoptosis was suppressed. These results suggest that the regulatory effects of irisin on cardiomyocyte activity and mitochondrial energy metabolism are mediated by FUNDC1 [ 164 ].…”
Section: Natural Medicinal Plants and Active Ingredients In The Regul...mentioning
confidence: 99%
“…Jiang (2021) (Jiang et al, 2021) Lipopolysaccharide-stimulated cardiomyocytes ↓Bax, caspase-3 and Fundc1…”
Section: Possible Mechanisms Of the Role Of Irisin In Ami Rehabilitationmentioning
confidence: 99%
“…Irisin is mainly secreted in skeletal ( Boström et al, 2012 ) and cardiac muscle tissue ( Aydin et al, 2014 ), and is implicated in modulation of mitochondrial function and energy balance ( Ouyang et al, 2020 ; Xin et al, 2020 ) lipid and glucose metabolism ( Perakakis et al, 2017 ; Wang et al, 2020 ), and amelioration of impaired cardiac function in some metabolic disorders ( Wang et al, 2017 ; Jiang et al, 2021 ). Previous findings show that circulating irisin level is lower in patients with chronic heart failure ( Silvestrini et al, 2019 ), middle cerebral artery occlusion (MCAO) patients ( Li et al, 2017 ), and subjects with Alzheimer disease (AD) ( Kim et al, 2018 ) compared with normal subjects.…”
Section: Introductionmentioning
confidence: 99%